Música integrando conhecimentos botânicos e ambientais - Teixeira, Janio Carlos Ramos (2018)
Botany is one of the oldest sciences applied by mankind and, in this sense, walks with a paradigm in relation to its applicability do not refer to theoretical / methodological approaches in the classroom, causing students to be uninterested due to the lack of contextualization and practical activities for an understanding of the importance of vegetables to the environment. This program is designed to develop didactic forms in the form of a musical repertoire for biology classes, using economics as Environmental Education. In this sense, the use of music as a resource can bring students closer to the themes through an approach that brings their socio-cultural universe closer to the proposed contents. NBA, as it refers to methodologies that guide research, are initially intended as diagnoses as environmental issues were developed during the school life with speeches of the course in Biological Sciences (LCB) and Technical High School Integrated in Chemistry (IQUI) of the Federal Institute of Science, Education and Technology of Amazonas - Campus Manaus Center (IFAM / CMC). In this way we will have information that is necessary for an application not High School and in the LCB training of teachers in terms of essential content for a basic training of teachers. Logo after an intervention process that consists of three stages. The first is to apply a theoretical lecture on the subject addressing as notions of basic medicine for the compression of the environment. The second step relates to an approach on engagement with music through the appreciation and manipulation of musical instruments. In the third stage will be built a repertoire by the students with music involving the theme. After previous steps, a musical didactic resource is developed so that biology teachers based on classroom contents from experience.